Challenges and lessons learned from four years of planning and implementing pharmacovigilance enhancement in sub-Saharan Africa - Jens-Ulrich Stegmann; Viviane Jusot; Olga Menang; Gregory Gardiner; Sabino Vesce; Stephanie Volpe; Anderson Ndalama; Felix Adou; Opokua Ofori-Anyinam; Olakunle Oladehin; Yolanda Guerra Mendoza (BMC, 2022)
Abstract Pharmacovigilance (PV) systems in many countries in sub-Saharan Africa (SSA) are not fully functional. The spontaneous adverse events (AE) reporting rate in SSA is lower than in any other region of the world, and healthcare professionals (HCPs) in SSA countries have limited awareness of AE surveillance and reporting procedures. The GSK PV enhancement pilot initiative, in collaboration with PATH and national PV stakeholders, aimed to strengthen passive safety surveillance through a training and mentoring program of HCPs in healthcare facilities in three SSA countries: Malawi, Côte d'Ivoire, and Democratic Republic of Congo (DRC). Project implementation was country-driven, led by the Ministry of Health via the national PV center or department, and was adapted to each country's needs. The implementation phase for each country was scheduled to last 18 months. At project start, low AE reporting rates reflected that awareness of PV practices was very low among HCPs in all three countries, even if a national PV center already existed. Malawi did not have a functional PV system nor a national PV center prior to the start of the initiative. After 18 months of PV training and mentoring of HCPs, passive safety surveillance was enhanced significantly as shown by the increased number of AE reports: from 22 during 2000-2016 to 228 in 18 months to 511 in 30 months in Malawi, and ~ 80% of AE reports from trained healthcare facilities in Côte d'Ivoire. In DRC, project implementation ended after 7 months because of the SARS-CoV-2 pandemic. Main challenges encountered were delayed AE report transmission (1-2 months, due mainly to remoteness of healthcare facilities and complex procedures for transmitting reports to the national PV center), delayed or no causality assessment due to lack of expertise and/or funding, negative perceptions among HCPs toward AE reporting, and difficulties in engaging public health programs with the centralized AE reporting processes. This pilot project has enabled the countries to train more HCPs, increased reporting of AEs and identified KPIs that could be flexibly replicated in each country. Country ownership and empowerment is essential to sustain these improvements and build a stronger AE reporting culture.